Risk factors of pulmonary tuberculosis among diabetes mellitus patients in Denpasar City - Desak Putu Risna Dewi; I Wayan Gede Artawan Eka Putra; Anak Agung Sagung Sawitri; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2017)
Background and Purpose: Tuberculosis (TB) is more common in developing countries, including Indonesia. Denpasar City contributes the most on the total number of TB patients in Bali Province. There is evidence on increased burden of diabetes mellitus (DM) patients with TB comorbidity. This study aims to examine risk factors of TB among DM patients. Method: A case control study was conducted in Denpasar City. A total of 135 samples, 45 cases and 90 controls, were recruited to participate in the study. Cases were DM patients with TB comorbidity and were taken from patients register from 2013 to 2015. Controls were DM patients without TB comorbidity and were taken from Bali Province screening operational study. Data were collected using interviews, observations, measurements and document review. Data were analysed using bivariate analysis and multivariate with logistic regression model. Results: Demographic characteristics between cases and controls were comparable in sex and family income but not comparable in age groups, education, domicile, and employment. Risk factors of TB among DM patients were house density (AOR=36.11; 95%CI: 5.0-259.9), undernutrition (AOR=24.76; 95%CI: 3.7-162.3), inadequate glycemic control (AOR=12.64; 95%CI: 2.4-66.2), and being employed (AOR=10.55; 95%CI: 1.2-92.7). TB infection among DM patients was associated with aged<60 years (AOR=7.47; 95%CI: 1.2-44.3) and being male (AOR=5.42; 95%CI: 1.2-24.0). TB co-infection among DM patients was also associated with low education level (AOR=6.96; 95%CI: 1.0-48.6), contact with TB patients (AOR=5.84; 95%CI: 0.7-46.6) and inadequate house ventilation (AOR=2.92; 95%CI: 0.6-13.1). Conclusion: Socio-demographic characteristics, physical environments of the house and clinical conditions are risk factors of TB among DM patiens.